2012
DOI: 10.1177/089875641202900404
|View full text |Cite
|
Sign up to set email alerts
|

The Development of an Oral Health Charting System for Koalas(Phascolarctos Cinereus)

Abstract: The koala is one of Australia's most highly specialized folivores with a diet exclusively of eucalyptus leaves to provide all nutritive needs and therefore requires to be free of oral disease as they are dependent on good dentition for optimal health and quality of life. We developed an oral examination methodology based on protocols for companion animals and human dentistry to chart the oral health of koalas. Thirty free-ranging koalas from South-East Queensland, Australia were examined for general body and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…Department employees provide veterinarian assessment and treatment, vegetation collection and facility maintenance (McKinnon, 2002). Trialling new veterinarian therapies, public relations and collaborations with researchers and similar Australian facilities are also ongoing functions of the staff (McKinnon, 2002, Lee et al, 2011, Pettett et al, 2012. Animals brought to the facility are diagnosed, treated and maintained after sustaining injury, disease or orphan status.…”
Section: The Moggill Koala Hospitalmentioning
confidence: 99%
“…Department employees provide veterinarian assessment and treatment, vegetation collection and facility maintenance (McKinnon, 2002). Trialling new veterinarian therapies, public relations and collaborations with researchers and similar Australian facilities are also ongoing functions of the staff (McKinnon, 2002, Lee et al, 2011, Pettett et al, 2012. Animals brought to the facility are diagnosed, treated and maintained after sustaining injury, disease or orphan status.…”
Section: The Moggill Koala Hospitalmentioning
confidence: 99%
“…Oral cavity and dental health examinations are poorly described in koalas. Deviations from normal occlusion were first detected in several Queensland koalas in an earlier study by Pettett et al . The koala dentition consists of 30 herbivorous teeth designed to masticate tough eucalyptus leaves which is the complete diet of the koala.…”
Section: Introductionmentioning
confidence: 99%
“…The canines do not occlude with any other teeth while the incisal edge of the mandibular incisors occlude against the incisal edge of the second maxillary incisors. A slight overlap towards the third maxillary incisors may occur and appears to be the norm . The jaw alignment is anisognathic, where the maxilla is wider than the mandible.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many studies determining which of the causative agent(s) initiate oral diseases in humans and domesticated animals. Marsupials also have oral diseases 3,4 and culture-dependent studies have shown a range of bacteria can be isolated from the marsupial oral cavity 5 . However culture-based studies, while useful to enable precise characterisation of putative periodontopathogens, generally underestimate microbial community diversity.…”
mentioning
confidence: 99%
“…Koalas do present with severe periodontal disease 4 and with severe loss of alveolar bone associated with age and conditions such as food impaction 3 ( Figure 1). In koalas <7 years old with good oral health, there was an absence of black-pigmented bacteria, compared to koalas >7 years of age, where 50% harboured black-pigmented bacteria, the majority of which were identified as Porphyromonas gingivalis-like 14 .…”
mentioning
confidence: 99%